E-HAILING SERVICES IN MALAYSIAâ€: A SNAPSHOT OF LEGAL ISSUES AND RISKS (Revista Galega de Economía)
The rise of e-hailing services such as Grab and MyCar has overshadowed public transportation in Malaysia. E-hailing is a transport service that allows passengers to book a trip in real time using virtual devices such as mobile phones. E-hailing platforms are predicted to grow tremendously as consumers continue to demand them for their convenience, speed, and cost-saving benefits. Beginning October 2019, Malaysian e-hailing operators have been subject to control-oriented laws similar to those imposed on taxi drivers. This article attempts to highlight the regulatory framework that governs e-hailing services in Malaysia, as well as the legal issues and risks that e-hailing services face. It employs qualitative legal research, emphasising the study of law and the use of web, print, scholarly, and government statistics. The data were structured using theme analysis to generate a discussion narrative regarding e-hailing services in Malaysia, taking into consideration multiple viewpoints on the regulatory framework, legal concerns, and risks of this industry. It is found that despite the existence of essential laws that legalise e-hailing services, it has been discovered that legal concerns concerning legal status, safety, privacy, and liability persist in Malaysia's e-hailing services. On the one hand, there is a genuine urgency to ensure users' safety, which must not be suffocated by harsh and overbearing law. As a result, understanding legal reactions to e-hailing services and exploring innovative approaches to handle growing legal difficulties is critical.